Electrical and optical characterization of bis(7-methoxybenzofuran-2-il)ketone - Dagdelen, F.; Koca, M.; Kirilmis, C.; Aydogdu, Y. (Amer Inst Physics, 2007)
The electrical and optical properties of Bis(7-methoxybenzofuran-2-il)ketone have been experimentally characterized. The optical band gap of Bis(7-methoxybenzofuran-2-il)ketone was found as 2.76 eV. Single-oscillator energy and dispersion energy of the sample were calculated by plotting (n(2)-1)(-1)-(h upsilon)(2) and found as 4.58 eV and 28 eV, respectively. The refractive index for long wavelength values (n(infinity)) and the ratio of carrier concentration to the effective mass(N/m*) were obtained as 2.41 and 4.36 10(48) g(-1) cm(-3), respectively.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY
Keywords: optical properties; reflectance; single-oscillator energy